# Class 12 RD Sharma Solutions – Chapter 19 Indefinite Integrals – Exercise 19.9 | Set 1

### Evaluate the following integrals:

### Question 1. ∫(logx)/x dx

**Solution:**

Given that, I = ∫(logx)/x dx

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.Let us considered logx = t

Now differentiating both side we get,

d(logx) = dt

1/x dx = dt

dx = xdt

Then, put logx = t and dx = xdt, we get

I = ∫ t/x × (x)dt

= ∫ tdt

= t

^{2}/2 + c= (logx)

^{2}/2 + cHence, I = (logx)

^{2}/2 + c

### Question 2.∫(log(1 + 1/x))/(x(1 + x)) dx

**Solution:**

Given that I = ∫(log(1 + 1/x))/(x(1 + x)) dx ……(i)

Let us considered log(1 + 1/x) = t then

On differentiating both side we get,

d[log(1 + 1/x)]=dt

1/(1 + 1/x) × (-1)/x

^{2}dx = dt1/((x + 1)/x) × (-1)/x

^{2}dx = dt(-x)/(x

^{2}(x + 1)) dx = -dtdx/(x(x + 1)) = -dt

Now, on putting log(1 + 1/x) = t and dx/(x(x + 1)) = -dt in equation (i), we get

I = ∫t × -dt

= -t

^{2}/2 + c= -1/2 [log(1 + 1/x)]

^{2 }+ cHence, I = -1/2 [log(1 + 1/x)]

^{2 }+ c

### Question 3. ∫((1 + √x )^{2})/√x dx

**Solution:**

Given that I = ∫((1 + √x)

^{2})/√x dxLet us considered (1 + √x) = t then,

On differentiating both side we get,

d(1 + √x) = dt

1/(2√x) dx = dt

dx = dt × 2√x

Now on putting (1 + √x) = t and dx = dt × 2√x, we get

I = ∫t

^{2}/√x × dt × 2√x= 2∫t

^{2}dt= 2 × t

^{3}/3 + c= 2/3[1 + √x]

^{3 }+ cHence, I = 2/3(1 + √x)

^{3 }+ c

### Question 4. ∫√(1 + e^{x}) e^{x} d

**Solution:**

Given that I = ∫√(1 + e

^{x}) e^{x }dx ……(i)Let us considered 1 + e

^{x }= t then,On differentiating both side we get,

d(1 + e

^{x}) = dte

^{x}dx = dtdx = dt/e

^{x}Now on putting 1 + e

^{x }= t and dx = dt/e^{x}in equation (i), we getI = ∫√t × e

^{x}× dt/e^{x}= ∫ t

^{1/2}dt= 2/3t

^{3/2 }+ c= 2/3 (1 + e

^{x})^{3/2}+c

### Question 5. ∫∛(cos^{2}x) sinx dx

**Solution:**

Given that I = ∫∛(cos

^{2}x) sinx dx ……(i)Let us considered cosx = t then,

On differentiating both side we get,

d(cosx) = dt

-sinxdx = dt

dx = -dt/(sinx))

Now on putting cosx = t and dx = -dt/(sinx) in equation (i), we get

I = ∫∛(t

^{2}) sinx × (-dt)/(sinx)= -∫t

^{2/3}sinx dt/(sinx)= -∫ t

^{2/3}dt= -3/5 × t

^{5/3}Hence, I = -3/5(cosx)

^{5/3 }+ c

### Question 6. ∫e^{x}/(1 + e^{x})^{2} dx

**Solution:**

Given that I = ∫e

^{x}/(1 + e^{x})^{2 }dx …….(i)Let us considered 1 + e

^{x }= t then,On differentiating both side we get,

d(1 + e

^{x}) = dte

^{x}dx = dtdx = dt/e

^{x}Now on putting 1 + e

^{x }= t and dx = dt/e^{x }in equation (i), we getI = ∫e

^{x}/t^{2}× dt/e^{x}= ∫dt/t

^{2}= ∫t

^{-2}dt= -t

^{-1 }+ c= -1/t + c

= -1/(1 + e

^{x}) + cHence, I = -1/(1 + e

^{x}) + c

### Question 7. ∫cot^{3}x cosec^{2}x dx

**Solution:**

Given that I = ∫cot

^{3}x cosec^{2}x dx …….(i)Let us considered cotx = t then,

On differentiating both side we get,

d(cotx) = dt

-cosec

^{2}x dx = dtdx = -dt/cosec

^{2}xNow on putting cotx = t and dx = -dt/(cosec

^{2}x) in equation (i), we getI = ∫ t

^{3 }cosec^{2}x × (-dt)/(cosec^{2}x)= -∫ t

^{3}dt= -t

^{4}/4 + c= -(cot

^{4}x)/4 + cHence, I = -(cot

^{4}x)/4 + c

### Question 8.

**Solution:**

Given that I =[Tex] [/Tex] …….(i)

Let us considered sin

^{-1}x = t then,On differentiating both side we get,

d(sin

^{-1}x) = dt1/√(1 – x

^{2})dx = dtdx = √(1 – x

^{2}) dt)Now on putting sin

^{-1}x = t and dx = √(1 – x^{2}) dt in equation (i), we getI = ∫ (e

^{t})^{2}/√(1 – x^{2}) × √(1 – x^{2}) dt= ∫e

^{2t}dt= e

^{2t}/2 + c= + c

Hence, I = + c

### Question 9. ∫(1 + sinx)/√(x – cosx) dx

**Solution:**

Given that I = ∫(1 + sinx)/√(x – cosx) dx ……..(i)

Let us considered x – cosx = t, then

On differentiating both side we get,

d(x – cosx) = dt

[1 – (-sinx)]dx = dt

(1 + sinx)dx = dt

Now on putting x – cosx = t and (1 + sinx)dx = dt in equation (i), we get

I = ∫ dt/√t

= ∫ t

^{-1/2}dt= 2t

^{1/2 }+ c= 2(x – cosx)

^{1/2 }+ cHence, I = 2√(x – cosx) + c

### Question 10. ∫1/(√(1 – x^{2}) (sin^{-1}x)^{2}) dx

**Solution:**

Given that I = ∫1/(√(1 – x

^{2}) (sin^{-1}x)^{2}) dx …..(i)Let us considered sin

^{-1}x = t then,On differentiating both side we get,

d(sin

^{-1}x) = dt1/√(1 – x

^{2}) dx = dtNow on putting sin

^{-1}x = t and 1/√(1 – x^{2}) dx = dt in equation (i), we getI = ∫dt/t

^{2}= ∫t

^{-2}dt= -t

^{-1 }+ c= (-1)/t + c

= (-1)/(sin

^{-1}x) + cHence, I = (-1)/(sin

^{-1}x) + c

### Question 11. ∫(cotx)/√(sinx) dx

**Solution:**

Given that I = ∫(cotx)/√(sinx) dx …….(i)

Let us considered sinx = t then,

On differentiating both side we get,

d(sinx) = dt

cosxdx = dt

Now, I = ∫(cotx)/√(sinx) dx

= ∫(cosx)/(sinx√(sinx)) dx

= ∫ cosx/(sinx)

^{3/2}dx= ∫ cosx/(sinx)

^{3/2}dx …….(ii)Now on putting sinx = t and cosxdx = dt in equation (ii), we get

I = ∫ dt/t

^{3/2}= ∫ t

^{-3/2}dt= -2t

^{-1/2 }+ c= -2/√t + c

= -2/√(sinx) + c

I = -2/√sinx + c

### Question 12. ∫(tanx)/√(cosx) dx

**Solution:**

Given that I = ∫(tanx)/√(cosx) dx

I = ∫sinx/cosx√(cosx) dx

= ∫ sinx/(cosx)

^{3/2}dx= ∫sinx/(cosx)

^{3/2}dx ……..(i)Let us considered cosx = t then,

On differentiating both side we get,

d(cosx) = dt

-sinxdx = dt

sinxdx = -dt

Now on putting cosx = t and sinxdx = -dt in equation (i), we get

I = ∫(-dt)/t

^{-3/2}= -∫t

^{-3/2}dt= -[-2t

^{-1/2}] + c= 2/t

^{1/2 }+ c= 2/√(cosx) + c)

Hence, I = 2/√(cosx) + c

### Question 13. ∫cos^{3}x/√(sinx) dx

**Solution:**

Given that I = ∫cos

^{3}x/√(sinx) dx= ∫(cos

^{2}xcosx)/√(sinx) dx= ∫((1 – sin

^{2}x)cosx)/√(sinx) dx= ∫((1 – sin

^{2}x))/√(sinx) cosxdx ……(i)Let us considered sinx = t then,

On differentiating both side we get,

d(sinx) = dt

cosxdx = dt

Now on putting sinx = t and cosxdx = dt in equation (i), we get

I = ∫(1 – t

^{2})/√t dt= ∫(t

^{-1/2}-t^{2}x t^{-1/2})dt=∫(t

^{-1/2 }– t^{3/2})dt= 2t

^{1/2 }– 2/5 t^{5/2 }+ c= 2(sinx)

^{1/2 }– 2/5(sinx)^{5/2 }+ cHence, I = 2√(sinx) – 2/5(sinx)

^{5/2 }+ c

### Question 14. ∫(sin^{3}x)/√(cosx) dx

**Solution**:

Given that I = ∫(sin

^{3}x)/√(cosx) dx= ∫(sin

^{2}xsinx)/√(cosx) dx=∫((1 – cos

^{2}x))/√(cosx) sinxdx …….(i)Let us considered cosx = t then,

On differentiating both side we get,

d(cosx) = dt

-sinxdx = dt

sinxdx = -dt

Now on putting cosx = t and sinxdx = -dt in equation (i), we get

I = ∫((1 – t

^{2}))/√t × -dt= ∫(t

^{2 }– 1)/√t dt= ∫(t

^{2}/t^{1/2}– 1/t^{1/2})dx= ∫(t

^{2-1/2 }– t^{-1/2})dt= ∫(t

^{3/2 }– t^{1/2})dt= 2/5 t

^{5/2 }– 2t^{1/2 }+ c= 2/5 cos

^{5/2}x – 2cos^{1/2}x + cHence, I = 2/5 cos

^{5/2}x – 2√(cosx) + c

### Question 15. ∫1/(√(tan^{-1}x) (1 + x^{2})) dx

**Solution:**

Given that I = ∫1/(√(tan

^{-1}x) (1 + x^{2})) dx …..(i)Let us considered tan

^{-1}x = t, thenOn differentiating both side we get,

d(tan

^{-1}x) = dt1/(1 + x

^{2}) dx = dtNow on putting tan

^{-1}x = t and 1/(1 + x^{2}) dx = dt in equation (i), we getI = ∫1/√t dt

= ∫t

^{-1/2}dt= 2t

^{1/2 }+ c= 2√tan

^{-1}x + cHence, I = 2√tan

^{-1}x + c

### Question 16. ∫√(tanx)/(sinxcosx) dx

**Solution:**

Given that I = ∫√(tanx)/(sinxcosx) dx

= ∫(√(tanx)×cosx)/(sinxcosx×cosx) dx

= ∫√(tanx)/(tanxcos

^{2}x) dx= ∫(sec

^{2}xdx)/√(tanx) dxLet us considered tanx = t, then

On differentiating both side we get,

sec

^{2}xdx = dtNow

I = ∫ dt/√t

= 2√t + c

Hence, I = 2√tanx + c

### Question 17. 1/x × (logx)^{2} dx

**Solution:**

Given that I = ∫1/x × (logx)

^{2}dx …..(i)Let us considered logx = t then,

On differentiating both side we get,

d(logx) = dt

1/x dx = dt

Now on putting logx = t and 1/x dx = dt in equation (i), we get

I = ∫t

^{2}dt= t

^{3}/3 + c= (logx)

^{3}/3 + cHence, I = (logx)

^{3}/3 + c

### Question 18. ∫sin^{5}x cosx dx

**Solution:**

Given that I = ∫sin

^{5}x cosx dx ……(i)Let us considered sinx = t then,

On differentiating both side we get,

d(sinx) = dt

cosxdx = dt

Now on putting sinx = t and cosxdx = dt in equation (i), we get

I = ∫ t

^{5}dt= t

^{6}/6 + c= (sin

^{6}x)/6 + cHencec, I = 1/6 (sin

^{6}x) + c

### Question 19. ∫tan^{3/2}x sec^{2}x dx

**Solution:**

Given that I = ∫tan

^{3/2}xsec^{2}xdx ……(i)Let us considered tanx = t then,

On differentiating both side we get,

d(tanx) = dt

sec

^{2}xdx = dtNow on putting tanx = t and sec

^{2}xdx = dt in equation (i), we getI = ∫ t

^{3/2}dt= 2/5 t

^{5/2 }+ c= 2/5(tanx)

^{5/2 }+ cHence, I = 2/5 tan

^{5/2}x + c

### Question 20. ∫(x^{3})/(x^{2 }+ 1)^{2}dx

**Solution:**

Given that I = ∫(x

^{3})/(x^{2 }+ 1)^{2}dx …….(i)Let us considered 1 + x

^{2 }= t then,On differentiating both side we get,

d(1 + x

^{2}) = dt2xdx = dt

xdx = dt/2

Now on putting 1 + x

^{2 }= t and xdx = dt/2 in equation (i),we getI = ∫x

^{2}/t^{3}× dt/2= 1/2∫(t – 1)/t

^{3}dt [1 + x^{2 }= t]= 1/2∫[(t/t

^{3}– 1/t^{3})dt]= 1/2∫(t

^{-2 }– t^{-3})dt= 1/2 [-1t

^{-1 }– t^{-2}/(-2)] + c= 1/2 [-1/t + 1/(2t

^{2})] + c= -1/2t + 1/(4t

^{2}) + c= -1/2(1 + x

^{2}) + 1/(4(1 + x^{2})^{2}) + c= (-2(1 + x

^{2}) + 1)/(4(1 + x^{2})^{2}) + c= (-2 – 2x

^{2 }+ 1)/(4(1 + x^{2})^{2}) + c= (-2x

^{2 }– 1)/(4(1 + x^{2})^{2}) + c= -(1 + 2x

^{2})/(4(x^{2 }+ 1)^{2}) + cHenec, I = -(1 + 2x

^{2})/(4(x^{2 }+ 1)^{2}) + c

### Question 21. ∫(4x + 2)√(x^{2 }+ x + 1) dx

**Solution:**

Given that I = ∫(4x + 2)√(x

^{2 }+ x + 1) dxLet us considered x

^{2 }+ x + 1 = t then,On differentiating both side we get,

(2x + 1)dx = dt

Now,

I = ∫ (4x + 2)√(x

^{2 }+ x + 1) dx= ∫2√t dt

= 2∫√t dt

= 2t

^{3/2}/(3/2) + cHence, I = 4/3 (x

^{2 }+ x + 1)^{3/2 }+ c

### Question 22. ∫(4x + 3)/√(2x^{2 }+ 3x + 1) dx

**Solution:**

Given that l = ∫(4x + 3)/√(2x

^{2 }+ 3x + 1) dx ……(i)Let us considered 2x

^{2 }+ 3x + 1 = t then,On differentiating both side we get,

d(2x

^{2 }+ 3x + 1) = dt(4x + 3)dx = dt

Now on putting 2x

^{2 }+ 3x + 1 = t and (4x + 3)dx = dt in equation (i), we getI = ∫dt/√t

= ∫t

^{-1/2}dt= 2t

^{1/2 }+ c= 2√t + c

Hence, I = 2√(2x

^{2 }+ 3x + 1) + c

### Question 23. ∫1/(1 + √x) dx

**Solution:**

Given that I = ∫1/(1 + √x) dx …….(i)

Let us considered x = t

^{2}then,On differentiating both side we get,

dx = d(t

^{2})dx = 2tdt

Now on putting x = t

^{2 }and dx = 2tdt in equation (i), we getI = ∫2t/(1 + √(t

^{2})) dt= ∫2t/(1 + t) dt

= 2∫t/(1 + t) dt

= 2∫(1 + t – 1)/(1 + t) dt

= 2⌋[(1 + t)/(1 + t) – 1/(1 + t)]dt

= 2∫dt – 2∫1/(1 + t) dt

= 2t – 2log|(1 + t)| + c

= 2√x – 2log|(1 + √x)| + c

Hence, I = 2√x – 2log|(1 + √x)| + c

### Question 24.

**Solution:**

Given that I = …….(i)

Let us considered cos

^{2}x = t then,On differentiating both side we get,

d(cos

^{2}x) = dt-2cosx sinx dx = dt

-sin2x dx = dt

sin2x dx = -dt

Now on putting cos

^{2}x = t and sin2x dx = -dt in equation (i), we getI = ∫e

^{t}(-dt)= -e

^{t }+ c= – + c

Hence, I = – + c